PERENCANAAN PENGEMBANGAN DESA BUDAYA CIKONDANG MELALUI PENINGKATAN SARANA DAN PRASARANA - Yessy Andriyani, - (2009)
Cikondang village is village with culture of sunda which still holding firmly mores value order, so that Cikondang village in targeting as cultural village by local government of Sub-province Bandung. But along with cymbal as culture village is not in making balance to by expansion of facilities and basic facilities supporting for the operational as culture village as tourism area. Lack of facilities and basic facilities in Cikondang Culture Village is problems which must soon is finalized, because supporting facilities and infrastructures is beginning of an area to can be made tourism area which is balmy, and can reach purpose of wanted. From the problems, done research with using quantitative descriptive research method with aim to make is descriptive or image of from phenomenon happened in research area systematically, factual and accurate, then is laid open and interpreted, and connects causality at the time of research so that can formulate problems resolving. population of Research is village area Cikondang along with the public, because population coverage broadness of research, hence taken by research sample by the way of purposive sampling or election of sample with certain consideration, because research object character tending to homogeny, hence research sample taken is to custom chief government of village. Cikondang village having regional wide 4016,096 ha, with cold air temperature and has mountain region relief and still having cultural omissions in the form of the custom house and resident still very jelling with Sudanese culture this thing is perfect solidarity to be made cultural village as tourism area. Culture village concept is a rural region concept having culture of sunda and still holding firmly the culture values with implementation in to everyday life, through uniquely culture of everyday life of village public cikondang, expected able to generate tourism in the area. Arranges regional situating and location of facilities and basic facilities appropriate, like division of zonation ( service zone, prop zone, core zone ) and situating of supporting facilities which will make area Cikondang Culture Village to become area tourist acceptable and ideal culture by people world widely. So purpose of which wish to be reached to preserve culture sunda through endowment to coming generation and increases prosperity of reachable Cikondang resident.Keyword : Development, settlement, culture village, Culture, facilities and basic facilities